Children's Mental health: Current trends in the need for and provision of services in the Unired States - Johnson Grados, Judy (1998)
In the United States traditionally many children have gone unserved. This has been partly due to barriers in accessing services and the result of a fragmented and disorganized system of care. However, in the last two decades substantial progress has been made in adressing these problems. This article reviews the need for children's mental health services in the United States, and describes recent attempts to improve coordination and access to the children's mental health service system. The introduction of systems of care, the expansion of school-based services, and innovations in the provision of community services are discussed.